REPRESENTATION OF TERRORISM AFTER 9/11 IN KATHRYN BIGELOW AND MARK BOAL'S ZERO DARK THIRTY MOVIE - Maulina Putri, Mela; Faisal Syarifudin, Bunyamin; Suswanto, Deni (Paradigma: Jurnal Kajian Budaya, 2025)
Terrorism, as a global phenomenon, has been widely represented in various media, particularly in films. One of the films that represent terrorism is Zero Dark Thirty by Kathryn Bigelow and Mark Boal. This research aims to discuss the representation of terrorism in Kathryn Bigelow and Mark Boal's Zero Dark Thirty, employing a qualitative approach and an analytical descriptive method. To achieve the research objectives, the author employs John Fiske's Semiotics theory, which is divided into three levels: the reality level, the representation level, and the ideological level. The results and discussions in this study are presented through visual and narrative aspects, which encompass elements such as appearance, costume, environment, behavior, voice, camera techniques, music, and casting. Zero Dark Thirty represents an act of terrorism that is following real conditions in the world. The film portrays acts of terrorism such as shootings and bombings—including suicide attacks—which result in fatalities, material losses, and widespread trauma. These elements contribute to reinforcing stereotypes of terrorism associated with Middle Eastern countries and the conflicts surrounding them. Critical awareness is necessary when watching because, as a media product, television or film serves to convey information, ideology, ideas, or propaganda that supports the dominant interests in society. In the film Zero Dark Thirty, the dominant interest refers to American interests, which provide a single perspective on the topic of terrorism. This study highlights the importance of critical awareness in consuming media, as films play a significant role in shaping public perceptions of terrorism and global conflicts.